A user control framework for cloud data migration in software as a service - Injuwe, Danga Imbaji; Ibrahim, Hamidah; Sidi, Fatimah; Ishak, Iskandar (Science and Information Organization, 2024)
Cloud computing represents the overarching paradigm that enables organizations to leverage cloud services for data storage and application deployment. Nowadays, organizations that use the cloud services can migrate their data using software as a service (SaaS). The organizations’ data and application are deployed over the cloud through the cloud data migration process of the on-premise to cloud migration; referring to the transition process from the legacy, locally hosted systems to cloud environment. Several data migration frameworks have emerged to guide users in the migration process. While numerous studies have addressed the importance of granting control to users during the cloud data migration process, a user control framework is yet to be created. Thereby, depriving user of visibility and sense of ownership, customization to meet users need, compliance and governance, and training. This paper aims at achieving this by proposing a conceptual user control framework for cloud data migration process in SaaS. The framework is constructed based on a comprehensive analysis conducted over existing research works that are related to cloud data migration with the aim to identify the steps/phases of data migration process, the factors affecting the user control with regard to the identified phases, and the control metrics of each identified factor. An initial conceptual user control framework is constructed based on the analysis of the literatures and further enhancement of the framework is made based on the expert reviews. © (2024), (Science and Information Organization). All Rights Reserved.